Deep investigation of neutral gas origins (DINGO): H i stacking experiments with early science data. Issue 3 (26th October 2022) - Rhee, Jonghwan; Meyer, Martin; Popping, Attila; Bellstedt, Sabine; Driver, Simon P; Robotham, Aaron S G; Whiting, Matthew; Baldry, Ivan K; Brough, Sarah; Brown, Michael J I; Bunton, John D; Dodson, Richard; et al.
ABSTRACT: We present early science results from Deep Investigation of Neutral Gas Origins (DINGO), an $\rm H$ i survey using the Australian Square Kilometre Array Pathfinder (ASKAP). Using ASKAP subarrays available during its commissioning phase, DINGO early science data were taken over ∼60 deg 2 of the Galaxy And Mass Assembly (GAMA) 23 h region with 35.5 h integration time. We make direct detections of six known and one new sources at z < 0.01. Using $\rm H$  i spectral stacking, we investigate the $\rm H$  i gas content of galaxies at 0.04 < z < 0.09 for different galaxy colours. The results show that galaxy morphology based on optical colour is strongly linked to $\rm H$  i gas properties. To examine environmental impacts on the $\rm H$ i gas content of galaxies, three subsamples are made based on the GAMA group catalogue. The average $\rm H$ i mass of group central galaxies is larger than those of satellite and isolated galaxies, but with a lower $\rm H$ i gas fraction. We derive a variety of $\rm H$ i scaling relations for physical properties of our sample, including stellar mass, stellar mass surface density, NUV − r colour, specific star formation rate, and halo mass. We find that the derived $\rm H$ i scaling relations are comparable to other published results, with consistent trends also observed to ∼0.5 dex lower limits in stellar mass and stellar surface density. The cosmic $\rm H$ i densities derived from our data are consistent with other published values at similar redshifts. DINGO early science highlights the power of $\rm H$ i spectral stacking techniques with ASKAP.